The "Harbinger of Chaos": Semantic Anatomy of a Simulacrum - Kolesnyk, Oleksandr (Studia Philologica, 2025)
This article analyses a number of statements delivered by E. Musk in mass media interviews and posted via the Twitter / X platform. The paper argues that the discursive statements under analysis do not meet the criterion of truth and therefore are identified as simulacra. The article focuses on the reconstruction of propositions that generate false senses in the said statements. The paper provides typological semiotic and functional characteristics of respective language units. Special attention is paid to the reconstruction of a "virus program" encoded in Musk's statement on empathy. The statement's inner "textual structure" and its frame representation are suggested. Interdisciplinary interpretations are carried out in the framework of the myth-oriewnted semiosis theory.